Determinants of Personal Financial Management of the Millennial Generation with Self-Control as Moderation - Adinda Azzahra; Rifa'atul Maftuhah; Rahila Ummah (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
The purpose of this study was to examine the influence of financial literacy (X1) and work environment (X2) on the personal financial management (Y1) of Millennials in Surabaya, with self-control (M1) as a moderating factor. The findings indicate that the work environment (X2) has a positive effect on financial management (Y1), and this effect is strengthened by self-control (M1). Financial literacy (X1) has a negative effect on financial management (Y1). Self-control (M1) is unable to moderate (strengthen/weaken) this effect. The research model strongly explains the independent variable (96%), but only explains 5.4% of the variation in personal financial management. The implication is that psychological and cultural factors in the workplace are more influential than financial knowledge for Millennials. A contextual and interactive financial literacy education strategy, accompanied by self-control training, is needed so that knowledge can be applied in managing personal finances.